Stock Split On The Liquidity Effect and Stock Return in Jakarta Stock Exchange - Yuniartha, Francisca; Susilowati, Soffy; Sutrisno, Wang (Management, 2010)
Research on stock splits has frequently been undertaken. The results vary, but fundamentally can be classified into two groups. First, the stock split is purely ”cosmetic”. Second, the stock split has a real effect on stocks. The difference between these opinions raises controversy. The purpose of this study is to examine whether stock splits influence stock liquidity and return of an individual stock as well as in a group of stocks as a portfolio. Overall, the results of this study show that stock splits did influence stock price, trading volume and bid–ask spread but did not influence stock risk and abnormal return from the point of view of an individual stock as well as in a group of stocks as a portfolio. The test of a relationship between bid–ask spread and stock price, trading volume and stock risk for each stock shows that all three variable did not significantly affect the bid–ask spread. On the other hand, the test of a relationship in a portfolio reveals that only stock prices significantly affect the bid–ask spread. Keywords: stock splits, liquidity, abnormal return, bid – ask spread, stock return